CD44 receptor targeted ‘smart’ multi-walled carbon nanotubes for synergistic therapy of triple-negative breast cancer - Singhai, Nidhi Jain; Maheshwari, Rahul; Ramteke, Suman (Colloid and interface science communications, 2020)
Triple-negative breast cancer requires high treatment specificity and efficacy due to its aggressive nature. In the present investigation, multi-walled carbon-nanotubes (MWCNTs) were functionalized using Hyaluronic acid (HA) and α-Tocopheryl succinate (α-TOS) and loaded with Doxorubicin (Dox) to obtained novel α-TOS-HA-MWCNTs/Dox conjugate to achieve enhanced cellular-placement and anticancer-therapeutic action against CD44 receptors overexpressing TNBC cells (MDA-MB-231). Interestingly, α-TOS-HA-MWCNTs/Dox displayed high cellular uptake as compared to individually tailored MWCNTs formulations. Anticancer investigation revealed prominent growth inhibition effect (SRB assay; GI50; 0.810 ± 0.017; p < .001) and high total apoptotic ratio (Annexin V/PI assay; 52.69 ± 4.86%; p < .005) in the MDA-MB-231 cells treated using α-TOS-HA-MWCNTs/Dox as compared to other formulations. Findings suggest that HA and α-TOS could be employed as a synergistic, safe, and effective tumor-targeted chemotherapy. [Display omitted] •Triple-negative breast cancer (TNBC) requires high treatment specificity and efficacy.•This investigation was aimed to design and deliver novel synergistic and targeted therapy for TNBC.•We utilized the HA (CD44 receptor targeting ligand), α-TOS (synergistic effect) and Dox (chemotherapeutic agent).•Dox was delivered via MWCNTs as drug delivery platform.